Key questions to ask before implementing a Digital Mental Health Service (DMHS): A primer for policy makers - Nickolai Titov; Blake F. Dear; Lauren Staples; Alana Fisher; Heather D. Hadjistavropoulos; Olav Nielssen (Internet Interventions)
Background: The proven success of treating high prevalence mental disorders via the internet by digital mental health services (DMHSs) has created enormous interest in the implementation of these services. In response, there are now excellent guides to support the “how” of DMHS implementation. Method: Drawing on the authors' experiences of successfully implementing high volume DMHSs and reflecting on planning sessions with decision makers and funders, the authors identified important questions that should be considered by policy makers, funders and healthcare managers before implementing a DMHS. These questions are more concerned with the “why” of implementation and are questions not typically examined or discussed in existing implementation guides and frameworks. Results: The authors describe eleven questions categorised by theme: 1. The nature of mental health and treatments, 2. The nature of DMHSs, and 3. Governance and eco-system. Questions include which mental health conditions to address, whether the condition even requires treatment, what type of services should be offered, where would the DMHS fit into the broader mental health system, how will they integrate with other health services, what is the optimal funding model, how will they employ technology, and what governance is required. Conclusions: Policy makers and funders have the challenging task of determining resource allocation among competing priorities in a complex and ever-changing world. We propose that navigating the complexities of DMHSs can be facilitated by developing a robust program logic that addresses these and other important questions. It is noted that the long-term success DMHSs requires not only a clear vision and careful planning, but realistic and stable funding, and a commitment to ongoing evaluation and development.